Vetoing and Inaugurating Policy Like Others Do: Evidence on Spatial Interactions in Voter Initiatives - Frank Streif; Zareh Asatryan; Annika Havlik (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
A sizeable literature studies whether governments strategically interact with each other through policy-diffusion, learning, fiscal and yardstick competition. This paper asks whether, in the presence of direct democratic institutions, spatial interactions additionally result from voters' direct actions. The proposed mechanism is that the voters' actions in vetoing a decision or inaugurating a preferred policy by a binding initiative in their jurisdiction can potentially have spillover effects on the actions of voters and special interest groups of neighboring jurisdictions. Utilizing data on around 1,800 voter-petitions across over 12,000 German municipalities in 2002-09, we find that a jurisdiction's probability of hosting a petition is positively driven by the neighbors' direct democratic activity. These effects are persistent, and are stronger for more visible instruments of direct democracy. The interactions are also mostly driven by petitions in same or similar policy areas, and are stronger in towns with relatively more per capita newspapers.
Keywords: D72; D78; R50; 330